The asthma prediction rule to decrease hospitalizations for children with asthma. Issue 3 (June 2016) - Arnold, Donald H.; Sills, Marion R.; Walsh, Colin G.
Abstract : Purpose of review: The aim of the present review was to discuss the challenges around clinical decision-making for hospitalization of children with acute asthma exacerbations and the development, internal validation, and future potential of the asthma prediction rule (APR) to provide meaningful clinical decision-support that might decrease unnecessary hospitalizations. Recent findings: The APR was developed and internally validated using predictor variables available before treatment in the emergency department, and performed well to predict 'need-for-hospitalization.' Oxygen saturation on room air and expiratory phase prolongation were most strongly associated with need-for-hospitalization. Summary: Research on prediction rules in pediatric asthma is rare. We developed and internally validated the APR using clinically intuitive predictor variables that are available at the bedside. Before incorporation into electronic decision-support the APR must undergo external validation and an impact analysis to determine if use of this tool will change clinician behavior and improve patient outcomes.